Multicultural Voluntarism–The Second-Hand Shop in Bodø, Norway, as Arena for New Encounters - Magnussen, Tone (Nordic Journal of Migration Research, 2021)
The article explores how voluntary activities provide a variety of multicultural encounters among volunteers and migrants and seeks to investigate the potential of such multicultural encounters. In particular, the article focuses upon how encounters physically take place. As a particular kind of meeting that involves conflict and surprise, multicultural encounters represent a potential for people with different backgrounds to come together and develop intercultural understanding through interaction around common interests. Empirically, the article is based on long-term participatory observations in a second-hand store in the city of Bodø, Norway, that plays an important role in the community. Analyses include discussions of how encounters have the potential to rework and transform differences, as well as discussions of the uneasiness in encounters. Analyses point to the productiveness of encounters: their transformative power, from which respect, trust and dialogue are outcomes of negotiation over differences.